LncRNA-PAX8-AS1 Silencing Decreases Cell Viability, Enhances Apoptosis, and Suppresses Doxorubicin Resistance in Myeloid Leukemia via the miR-378g/ERBB2 Axis. (6th October 2022) - Song, Xiaolu; Chen, Yirui; Peng, Ye; Wang, Xiaogang; Zheng, Sujie; Shi, Fangfang; Lan, Jianping
Abstract : Objective . Considering the role of lncRNAs reported as regulators in acute myeloid leukemia (AML) progression, the current research aims to investigate the role of PAX8-AS1 in chemo-resistant AML. Methods . Human AML cells HL60 and human doxorubicin (ADM)-resistant AML cells (HL60/ADM cells) were used to establish in vitro models of chemo-sensitive AML and refractory/recurrent AML, respectively. CCK-8 assay and flow cytometry were used to determine cell resistance to ADM, viability, and apoptosis. PAX8-AS1, miR-378g, and ERBB2 expressions in the models and/or AML patients were quantified via qRT-PCR or Western blot. The miRNA/mRNA axis targeted by PAX8-AS1 was analyzed using Starbase, TargetScan, or GEO and validated through a dual-luciferase reporter assay. The expressions of Bcl-2, Bax, and C Caspase-3 in cells were quantitated by Western blot. Results . The highly expressed PAX8-AS1 was observed in AML patients and HL60 cells, which was more evident in refractory/recurrent AML patients and HL60/ADM cells. Compared with that in ADM-treated parental HL60 cells, the viability of ADM-treated HL60/ADM cells remained strong. PAX8-AS1 overexpression increased viability and Bcl-2 expression, while diminishing apoptosis, Bax, and C Caspase-3 expressions in HL60 cells. However, the abovementioned aspects were oppositely impacted by PAX8-AS1 silencing in HL60/ADM cells. PAX8-AS1 directly targeted miR-378g, whose expression pattern is opposite to that of PAX8-AS1 in AML. MiR-378g upregulation abrogated the effects of PAX8-AS1 overexpression on HL60 cells. MiR-378g downregulation offset PAX8-AS1 silencing-induced effects on HL60/ADM cells. Moreover, ERBB2 was recognized as the target of miR-378g, with a higher expression in HL60/ADM cells than in HL60 cells. Conclusion . PAX8-AS1 silencing decreases cell viability, enhances apoptosis, and suppresses ADM resistance in AML via regulating the miR-378g/ERBB2 axis.